2005
DOI: 10.1269/jrr.46.249
|View full text |Cite
|
Sign up to set email alerts
|

Aml1 Gene Rearrangements and Mutations in Radiation-Associated Acute Myeloid Leukemia and Myelodysplastic Syndromes

Abstract: Several studies suggested a causal link between AML1 gene rearrangements and both radiation-induced acute myeloid leukaemia (AML) and myelodysplastic syndromes (MDS). Fifty-three AML samples were analyzed for the presence of AML1 abnormalities using fluorescent in-situ hybridization (FISH) and reverse transcription polymerase chain reaction (RT-PCR). Of these patients, 24 had experienced radiation exposure due to the Chernobyl accident, and 29 were non-irradiated spontaneous AML cases and served as controls. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Gluzman (1996) demonstrated the similarity of symptoms and characteristics of radiation-associated and spontaneous disease. Other groups have described the distinctive features of leukemic cells and myelodysplastic pre-leukemic stage of the radiation-associated acute myeloid leukemia (AML) (Bebeshko et al 1991(Bebeshko et al , 1999Klymenko et al 2005). Moreover, in a previous study we found that AML patients with the history of radiation exposure due to the Chornobyl accident were characterized by unfavorable clinical course and resistance to conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 82%
“…Gluzman (1996) demonstrated the similarity of symptoms and characteristics of radiation-associated and spontaneous disease. Other groups have described the distinctive features of leukemic cells and myelodysplastic pre-leukemic stage of the radiation-associated acute myeloid leukemia (AML) (Bebeshko et al 1991(Bebeshko et al , 1999Klymenko et al 2005). Moreover, in a previous study we found that AML patients with the history of radiation exposure due to the Chornobyl accident were characterized by unfavorable clinical course and resistance to conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 82%
“…A preliminary study of the same cohort of patients showed that the JAK2 V617F mutation was less common in IR-exposed PMF patients than in unexposed PMF patients. 1,19 Thus, we hypothesized that IR-exposed MPN patients would exhibit a lower rate of the usual driver mutations, but would exhibit novel mutations and genomic alterations which could contribute to MPN development and evolution. In this study, we confirmed this hypothesis and identified combinations of sequence variants and copy number variants that may serve as drivers of MPN in IR-exposed patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study we found that AML patients with a history of radiation exposure due to the Chernobyl accident exhibited AML-specific translocations affecting the AML1 and MLL loci less frequently as compared to spontaneous or topoisomerase II inhibitor-related AML cases [6,7]. We have now expanded our investigations to include the analysis of the gains and losses of chromosomal material and the analysis of allelic changes or loss-of-heterozygosity (LOH), both to identify potential fingerprints of the radiation-etiology of this malignancy.…”
Section: Introductionmentioning
confidence: 99%